Analisis Faktor-Faktor Yang Mempengaruhi Minat Mahasiswa Program Studi Akuntansi Untuk Menjadi Guru - Maharani Putri Priyani; Ramadani Ladysie; Putri Kuning Sri Wedari; Mayang Saputri; Lince Lidia Sagala; Miya Dewi Suprihandari (PUTRA JAWA PUBLISHER, 2023)
This study aims to determine the factors that influence the interest of accounting students in the study program to pursue a career in teaching. A qualitative descriptive approach was used to collect data based on respondents' answers, enabling the identification of factors that shape the interest of accounting students in becoming teachers. The factors explored include internal factors such as motivation and perception, as well as external factors such as family and peer environment. The study population consists of accounting students from the class of 2022 at STIE Mahardika Surabaya. The findings reveal that the main factors influencing accounting students' interest in becoming teachers are their perception of the teaching profession and the influence of the family and peer environment. Ultimately, it can be concluded that perception is the most significant internal factor impacting their interest.